2016
DOI: 10.4049/jimmunol.1501205
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Insights into the Multiple Sclerosis Risk Gene ANKRD55

Abstract: An intronic variant in ANKRD55, rs6859219, is a genetic risk factor for multiple sclerosis, but the biological reasons underlying this association are unknown. We characterized the expression of ANKRD55 in human PBMCs and cell lines. Three ANKRD55 transcript variants (Ensembl isoforms 001, 005, and 007) could be detected in PBMCs and CD4+ T cells but were virtually absent in CD8+, CD14+, CD19+, and CD56+ cells. Rs6859219 was significantly associated with ANKRD55 transcript levels in PBMCs and CD4+ T cells and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…However, these identified susceptibility genes do not fully account for the genetic pathogenesis of DM/PM-ILD. ANKRD55 has been shown to be inducible following inflammatory stimuli, and its expression may also increase susceptibility to inflammation in patients [29]. An increase in the protein expression of ANKRD55 in autoimmune encephalomyelitis mice suggests that this molecule may act as a disease biomarker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these identified susceptibility genes do not fully account for the genetic pathogenesis of DM/PM-ILD. ANKRD55 has been shown to be inducible following inflammatory stimuli, and its expression may also increase susceptibility to inflammation in patients [29]. An increase in the protein expression of ANKRD55 in autoimmune encephalomyelitis mice suggests that this molecule may act as a disease biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…ANKRD55 encodes ankyrin repeat domain-containing protein 55, which mediates protein-protein interactions. A recent report has revealed that ANKRD55 can be detected in resting CD4+ T cells and monocytes and may have possible relevance to autoimmune diseases (http://www.amazonia.transcriptome.eu) [29]. However, the exact function of ANKRD55 remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have underscored pleiotropy of ANKRD55 by linking SNPs in this locus to Crohn's Disease (7, 8), type 1 diabetes (9), juvenile idiopathic arthritis (10), celiac disease (11) and inflammatory myopathies (polymyositis and dermatomyositis) (12, 13), as well as post-traumatic stress disorder (14), cognitive decline in Alzheimer's disease (15), and type 2 diabetes (16, 17). Rs6859219 is significantly associated with expression levels of three ANKRD55 transcripts, i.e., Ensembl (GRCh37.p13 Human Genome Assembly) full-length protein isoform 001, shorter protein isoform 005 and non-coding transcript 007 in PBMCs, and 001 and 005 in CD4 + T cells (18), and acts thus as a cis-expression quantitative trait locus ( cis -eQTL). Rs71624119 (19) as wells as rs10065637 (20), a perfect proxy of rs6859219, were independently identified as cis -eQTLs for ANKRD55 expression, the latter so by means of multiple tagging probes.…”
Section: Introductionmentioning
confidence: 99%
“…Rs71624119 (19) as wells as rs10065637 (20), a perfect proxy of rs6859219, were independently identified as cis -eQTLs for ANKRD55 expression, the latter so by means of multiple tagging probes. The risk alleles of associated eQTL SNPs such as rs6859219, rs71624119 and rs10065637 are shared among autoimmune diseases and are associated with higher expression of ANKRD55 in CD4 + T lymphocytes (1820). Thus, ANKRD55 appears as the nearest annotated gene affected by the risk eQTL SNP rs6859219 or its proxies that emerged from GWAS on various autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A portion of target genes affected by risk QTLs code for proteins with as yet unknown or poorly understood biological functions, such as ANKRD55; hence, clarification from scratch of the biology of sometimes multiple co-produced isoforms is required. 7 In MS, cellular targets to be scrutinized by combinations of these and other approaches not only include cells of the peripheral immune system, CD4 + T cells, and monocytes but also central nervous system (CNS)-resident cells such as microglia and activated astrocytes. [1][2][3] Thus, an elaborate and multipronged experimental design is needed to fully understand the biological repercussions of the causal variant starting from the associated variant.…”
mentioning
confidence: 99%